Political and trade of the Malacca sultanate and the ming dynasty XV-XVI century - Darmawan, Budi; Nazra, Endah Regita Cahyani; Rahmawati, Fitri; Hasibuan, Nur Anisah (UNIVERITAS PGRI MADIUN, 2024)
This research was conducted due to the significance of the Malacca Strait's role as a trading center, connecting the Ming Dynasty in China with various regions, which led to economic growth and cultural interaction in Malacca. The main focus of the research lies on the political and trade interdependence between the Sultanate of Malacca and the Ming Dynasty during the 15th-16th centuries. The author employs the historical methods of heuristics, source criticism, data interpretation and historiography to conduct an in-depth analysis of historical records and artifacts, with the aim of holistically investigating the political and trade interrelationships between the Ming Dynasty and the Malacca Sultanate. The research reveals that diplomatic visits and mutually beneficial trade strengthened the relationship between Malacca and China. Facing threats from Siam and Majapahit, Malacca sought refuge from the Ming Dynasty, and began a close relationship. Notably, the visit of Chinese envoy Yin C'ing in 1403 paved the way for the arrival of Admiral Cheng Ho in 1409, which strengthened diplomatic relations. This relationship not only protected Malacca, but also facilitated its thriving trade. Malacca became a trading hub, offering China access to spices, while the Ming Dynasty provided military protection. The interdependence between Malacca and China in the 15th century underscores that their relationship not only fostered political security, but also increased trade and cultural exchange in the region.